2005
DOI: 10.1002/bip.20419
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the acidic and basic limbs of a bell‐shaped pH profile in the inhibitory activity of bromelain inhibitor VI

Abstract: Bromelain inhibitor VI (BI-VI) is a cysteine proteinase inhibitor from pineapple stem and a unique two-chain inhibitor composed of two distinct domains. BI-VI's inhibitory activity toward the target enzyme bromelain is maximal at pH 4 and shows a bell-shaped pH profile with pKa values of about 2.5 and 5.3. This pH profile is quite different from that of bromelain, which is optimally active around pH 7. In the present article, to characterize the acidic limb, we first expressed the recombinant inhibitors design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…2), indicating that the other residues in the heavy chain are not directly involved with proteinase inhibition. In previous studies (3,25), the carboxyl groups of the side chains of Asp 28 and Asp 51 were revealed to form hydrogen bonds with the (Fig. 1A).…”
Section: Site-directed Mutagenesis Of the Lightmentioning
confidence: 82%
“…2), indicating that the other residues in the heavy chain are not directly involved with proteinase inhibition. In previous studies (3,25), the carboxyl groups of the side chains of Asp 28 and Asp 51 were revealed to form hydrogen bonds with the (Fig. 1A).…”
Section: Site-directed Mutagenesis Of the Lightmentioning
confidence: 82%
“…wt.= 163), it may have a better penetration through the mucinous mass. Therefore, we investigated the mucolytic efficiacy of cysteamine in combination with bromelain that contains a number proteolytic enzymes [20,21]. Since there is an inter-patient variability in hardness of PMP mucin, we have classified patient mucin samples into three categories (soft, semi hard and hard) [10].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review on the anticancer properties of bromelain have emphasized that its proteolytic component may be mainly responsible for its anti-tumour effect [32]. Since, bromelain contains a number of other components such a cellulases, phosphatases, hydroxylases [33][34][35], along with a number of other protein components, the antitumor properties cannot be singly attributed to its proteolytic activity. Since, bromelain hydrolyses glycosidic linkages in glycoproteins [36]; it is inevitable that glycosylated moieties that J Glycobiology…”
Section: Introductionmentioning
confidence: 99%